Dignity : a journal on sexual exploitation and violence - University of Rhode Island (Department of Women's Studies, University of Rhode Island, 2016)
"'Dignity: A Journal on Sexual Exploitation and Violence' is an open access, peer-reviewed, interdisciplinary journal dedicated to publishing original scholarly articles on topics related to sexual exploitation, violence, and slavery. The journal is a forum for research, discussion, and analysis on how these forms of violence harm the dignity and health of individuals, the integrity and security of communities, and the strength and character of nations."
Keywords: Sex crimes : Study and teaching (Higher) : Periodicals; Violence : Study and teaching (Higher) : Periodicals; Slavery : Study and teaching (Higher) : Periodicals; Violence : Study and teaching (Higher)